Dynamics of fluid-filled space multibody systems considering the microgravity effects. (June 2020) - Kong, Weizhen; Tian, Qiang
Highlights: The dynamics of fluid-filled multibody systems is studied. The effects of microgravity accelerations are considered. A multiphase SPH scheme is used to describe the fluid-gas interaction. Some new nonlinear sloshing dynamics behaviors are observed. Abstract: Many fluid-filled multibody systems have been used in the aerospace field. Many previous studies on the dynamics of these systems did not consider the microgravity acceleration effects. Under the microgravity acceleration action the fluid surface tension plays a dominant role in system's complex sloshing dynamic responses. An integrated computational methodology is proposed to study the nonlinear sloshing dynamics of fluid-filled space multibody systems under the actions of microgravity accelerations. The Smoothed Particle Hydrodynamics (SPH) method is used to describe the fluid and the absolute nodal coordinate formulation (ANCF) is used to describe the flexible bodies. To consider the liquid-gas interaction in the container of the fluid-filled multibody systems, a multiphase SPH model is adopted. The continuum surface force (CSF) model is adopted to treat the liquid-gas interface tension effects. A liquid static contact angle is defined to describe the liquid-solid contact interface. Finally, the effectiveness of the proposed methodology is validated by the four examples. Some new nonlinear sloshing dynamical behaviours of the space liquid-filled flexible multibody systems under the action of different gravitational accelerations are observed.